Aplicação de técnicas eletroquímicas na determinação do potencial de corrosividade de ligas de alumínio em água produzida - Cunha, Jardel Dantas da (2012)
The resistance of aluminum and their alloys, to the corrosion phenomenon, in aqueous solutions, is a result of the oxide layer formed. However, the corrosion process in the aluminum alloy is associated with the presence a second phase of particles or the presence of chloride ions which promote the disruption of the oxide layer located producing the corrosion process. On the other hand, the term water produced is used to describe the water after the separation of the oil and gas in API separators. The volumes of produced water arrive around 5 more times to the volume of oil produced. The greatest feature of the water is the presence of numerous pollutants. Due to the increased volume of waste around the world in the current decade, the outcome and the effect of the discharge of produced water on the environment has recently become an important issue of environmental concern where numerous treatments are aimed at reducing these contaminants before disposal. Then, this study aims to investigate the electrochemical corrosion behavior of aluminum alloy 6060 in presence of water produced and the influence of organic components as well as chloride ions, by using the electrochemical techniques of linear polarization. The modification of the passive layer and the likely breakpoints were observed by atomic force microscopy (AFM). In the pit formation potential around -0.4 to -0.8 V/EAg/AgCl was observed that the diffusion of chloride ions occurs via the layer formed with the probable formation of pits. Whereas, at temperatures above 65 °C, it was observed that the range of potential for thepit formation was -0.4 to -0.5 V/EAg/AgCl. In all reactions, the concentration of Al(OH)3 in the form of a gel was observed